Molecular characterisation of beta thalassaemia in patients from Sabah, Malaysia - Teh, Lai Kuan (2014)
Sabah has the largest number of β-thalassaemia major (β-TM) patients in Malaysia with estimated over 1000 cases of transfusion dependent β-TM patients. However,complete molecular characterisation of thalassaemia major patients has not been done. The objective for this study is to characterise the molecular spectrum in Sabah population through β- and α-globin gene genotyping, identifying XmnI Gγ-polymorphism, haplotyping for β-globin gene cluster and to develop an ideal diagnostic algorithm and tools which is suitable for this population. In this study, 252 β-TM patients (Group I) and 165 carriers (Group II) were recruited from ten different hospitals in Sabah. Filipino β0-deletion was the predominant mutation identified in the Kadazandusun, Rungus, Murut, Sungai and Bajau. A total of 219 (86.9%) β-TM patients were identified as homozygous Filipino β0-deletion. HbE and Hb Malay were found as the most common Hb variants to co-inherit with Filipino β0-deletion. Some common mutations in West Malaysia were found to coexist with Filipino β0-deletion. This can be due to intermarriage between different ethnic groups. Carriers showed the frequency of Filipino β0-deletion at 95.2% (n=157). Only seven (4.2%) carriers were found with point mutations commonly seen in West Malaysia. High frequency of co-inheritance of -α3.7 deletion was found in the Sabah β-thalassaemia population. Co-inheritance of heterozygous -α3.7 deletion was found in 67 (26.6%) β-TM patients and 42 (25.3%) carriers. Co-inheritance of homozygous -α3.7 deletion was found in seven (2.8%) β-TM patients and six (3.6%) carriers. This may be related to the natural selection and protection for survival from severe malaria (Plasmodium Falciparum). Only type I of -α3.7 deletion was observed in this study population, indicating that the population has a single origin. XmnI Gγ polymorphism was reported with higher Gγ-globin gene expression. Clinical presentation will be ameliorated in homozygous states. In this study, XmnI (-/-) genotype was found in 237 (94%) β-TM patients and 156 (94.4%) carriers, indicating low existence of this polymorphism as an ameliorating factor. In haplotyping analysis, seven haplotype patterns were inferred in 417 samples consisting of 252 β-TM patients and 165 carriers. Hp I (+ - - - -) was the predominant pattern demonstrated in 98.14% of the population. This suggested a unicentric origin and an apparent single origin with low genetic diversity. This is the first report to demonstrate Hp I in the Sabah population with Filipino β0-deletion. Two new diagnostic tools, Taqman and HRM analysis were developed using realtime detection for Filipino β0-deletion. Taqman analysis was found more ideal as a diagnostic tool by having high specificity and sensitivity although it is more expensive. An added advantage is that there is no requirement for post-PCR processing. Multiplex ligation-dependent probe amplification (MLPA) analysis is an efficient technique for the screening of large deletions which can be included in the diagnosis algorithm provided technical expertise and necessary funding are available. This study reveals a notable regional specificity of the β- and α-thalassaemia mutations, which are Filipino β0-deletion and -α3.7 deletion. XmnI polymorphism is uncommon in this study population. From the haplotype analysis and type of -α3.7 deletion, the findings suggested that the Sabah population with β-thalassaemia may belong to the same stock with similar origin. Taqman analysis is more ideal as a diagnostic tool. The findings from this study are informative for molecular diagnosis in the Sabah population with β-thalassaemia.